MODERN APPROACHES FOR PROTECTION OF TRANSPORT STRUCTURES FROM INFLUENCES CAUSED BY MOVING DISPLACEMENTS AND FOR PROVIDING OF THEIR SAFE LONG TERM EXPLOITATION - Bresler, M. M.; Kosyak, V. M. (Science and Transport Progress, 2010)
The conception and new developments of Company «Maurer Soehne» intended for protection of transport structures from influences caused by displacements and for providing of their safe long-term exploitation are presented.